Caracterização microestrutural e análise de integridade estrutural de concretos pós-fogo em diferentes idades e temperaturas - Santos, Euler Wagner Freitas (2023)
Concrete is the most widely used material in building structures worldwide. Despite having high fire resistance, the structural stability of reinforced concrete buildings can be greatly compromised due to the loss of concrete integrity due to heat exposure resulting from fire accidents. The constituents of concrete have physical-chemical transformations with heat, directly influencing their mechanical strength. After a fire event, an adequate assessment of the integrity of concrete structures is essential, going beyond the exclusive use of visual inspection, and seeking to track the changes in the microstructure of the concrete that impact its mechanical properties. this study investigated the level of degradation of concretes of two classes of usual strengths in structures (C25 and C40), after being subjected to heating at three temperature levels (200 °C, 450 °C and 800 °C) for fire simulation, in two ages (100 days and 720 days). Cylindrical specimens were subjected to ultrasound tests, and subsequently ruptured under axial compression. Concrete samples from the fracture section were subjected to chemical analysis by Raman spectroscopy and x-ray diffraction (XRD), and morphological studies with scanning electron microscope (SEM). The results of SEM, Raman and XRD efficiently revealed the state of degradation of the concrete (by phase transformations, formation of pores and cracks), being compatible with the reductions of VPU and compressive strength with increasing temperature. These degradations, in turn, did not vary with the drying age and the strength class of the concrete.